2021
DOI: 10.1038/s41598-021-86819-6
|View full text |Cite
|
Sign up to set email alerts
|

A robust nitridation technique for fabrication of disordered superconducting TiN thin films featuring phase slip events

Abstract: Disorder induced phase slip (PS) events appearing in the current voltage characteristics (IVCs) are reported for two-dimensional TiN thin films produced by a robust substrate mediated nitridation technique. Here, high temperature annealing of Ti/Si3N4 based metal/substrate assembly is the key to produce majority phase TiN accompanied by TiSi2 & elemental Si as minority phases. The method itself introduces different level of disorder intrinsically by tuning the amount of the non-superconducting minority pha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Importantly, I c0 and I c nm are having different values and the resistive steps start from the base temperature for all the three magnetic fields. Therefore, PS effects get facilitated by the application of magnetic field as reported previously [15,16]. I c0 varies with temperature in a similar fluctuating trend for 75 mT as that of zerofield case, however, for higher field, the fluctuations smoothen up.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Importantly, I c0 and I c nm are having different values and the resistive steps start from the base temperature for all the three magnetic fields. Therefore, PS effects get facilitated by the application of magnetic field as reported previously [15,16]. I c0 varies with temperature in a similar fluctuating trend for 75 mT as that of zerofield case, however, for higher field, the fluctuations smoothen up.…”
Section: Resultssupporting
confidence: 74%
“…Disordered SCs in dirty limit with high normal state resistance (R N ) are the promising candidates for PS studies [14]. Recently, it has been shown that the transition metal nitrides are good candidates for PS studies [15,16]. Further, dilute magnetic doping is shown to trigger the PS events in NbGd films [8,17].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the sample specific characteristic parameters like Ta, film thickness (d), sheet resistance (Rmax) at Tmax before superconducting transition, superconducting critical temperature (Tc) as obtained by QCC fit, sheet resistance at 300 K (R300 K), upper critical field at T= 0 K (Bc2(0)), Diffusion constant (D) & the thermal coherence length (LT) at 100 K for all the TiN samples are listed in Table 1. Further, the presence of non-superconducting minority phases like TiSi2 & elemental Si in these substrate mediated TiN thin films [19] induces disorder and disordered 2D systems are ideal candidates where WL & EEI in diffusion channel (ID) play prominent roles for the appearance of an upturn and corresponding resistive peak at Tmax in the zero-field R(T). Inclined to this, we have followed here the 2D treatment with WL and EEI to address the observed upturn in the zero-field R(T).…”
Section: Resultsmentioning
confidence: 99%
“…Ti thin film deposited substrates were annealed at different annealing temperatures of about (820C, 780C & 750C) for 2 hours at a pressure less than 5 x 10 -8 Torr. During the annealing process, Ti transformed into TiN by the substrate mediated nitridation technique [18][19][20][21] where…”
Section: Methodsmentioning
confidence: 99%
“…Over the last few decades, disordered superconductors are at the center of attention in the field of condensed matter physics as they offer ideal platforms to explore various quantum phenomena such as quantum phase transition, quantum fluctuations, quantum criticality, quantum interference, quantum phase slip among the others [1,2]. In superconducting alloys and composite materials, the level of disorder can be easily tuned by changing the constituent elements and hence the transport properties can also be altered by tuning the composition [3][4][5].…”
Section: Introductionmentioning
confidence: 99%